2006
DOI: 10.1016/j.jmb.2006.09.074
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic Structure of Human Coronavirus NL63, One Thousand Years of Evolution

Abstract: Before the SARS outbreak only two human coronaviruses (HCoV) were known: HCoV-OC43 and HCoV-229E. With the discovery of SARS-CoV in 2003, a third family member was identified. Soon thereafter, we described the fourth human coronavirus (HCoV-NL63), a virus that has spread worldwide and is associated with croup in children. We report here the complete genome sequence of two HCoV-NL63 clinical isolates, designated Amsterdam 57 and Amsterdam 496. The genomes are 27,538 and 27,550 nucleotides long, respectively, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
158
2
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(179 citation statements)
references
References 52 publications
11
158
2
8
Order By: Relevance
“…The estimation of time of divergence was first extensively used in coronaviruses after the SARS epidemic for estimating the date of interspecies jumping of SARSr-CoV from civets to humans and that from BCoV to HCoV-OC43 [31,32]. Subsequently, when various novel human and animal coronaviruses were discovered, evolutionary rates and divergence time in the Coronaviridae family were estimated by various groups using different approaches [31,[33][34][35]. Although Bayesian inference in BEAST is probably the most widely accepted approach and was used by most researchers, the use of different genes (ORF1ab, helicase, S and N genes) and datasets by different groups have resulted in considerable difference in the estimated history of coronaviruses.…”
Section: Evolutionary Rate and Divergencementioning
confidence: 99%
“…The estimation of time of divergence was first extensively used in coronaviruses after the SARS epidemic for estimating the date of interspecies jumping of SARSr-CoV from civets to humans and that from BCoV to HCoV-OC43 [31,32]. Subsequently, when various novel human and animal coronaviruses were discovered, evolutionary rates and divergence time in the Coronaviridae family were estimated by various groups using different approaches [31,[33][34][35]. Although Bayesian inference in BEAST is probably the most widely accepted approach and was used by most researchers, the use of different genes (ORF1ab, helicase, S and N genes) and datasets by different groups have resulted in considerable difference in the estimated history of coronaviruses.…”
Section: Evolutionary Rate and Divergencementioning
confidence: 99%
“…In fact, recombination has been implicated in the sharing of homologous genes by distantly related members of the Coronaviridae family (14). Phylogenetic analyses have revealed that HCoV-NL63 may have undergone many recombination events, including two sites of recombination in the S gene and potential recombination between HCoV-NL63 and porcine enteric disease virus (PEDV) in the M gene (101). Additionally, evidence suggests that natural avian infectious bronchitis virus (AIBV) isolates recombined with a vaccine strain (Holland 52), specifically in the N gene (102).…”
Section: Recombinationmentioning
confidence: 99%
“…Human coronavirus NL63 (HCoV-NL63) is a relatively recently discovered human respiratory pathogen with a high worldwide prevalence (Fouchier et al, 2004;Golda & Pyrc, 2008;Hofmann et al, 2005;Pyrc et al, 2004Pyrc et al, , 2006Pyrc et al, , 2007aPyrc et al, , b, 2008Schildgen et al, 2006;van der Hoek et al, 2004 (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%